Estudo e análise do coeficiente de absorção acústico do compósito da fibra de cana - Outa, Roberto [UNESP] (2014)
The motivational goal of this work is to study the possibility of developing a material basis of bagasse with a higher added value, thus suggesting another function and / or use for bagasse from sugar cane. For this, we developed a cluster of sugarcane (composite) with different proportions of sugar and binder fiber and fiber were subsequently studied some acoustic characteristics of different composites, thus assessing the potential use of fiber as sound absorption material. The sound absorption coefficients of the cluster were estimated based on the theory and concepts of acoustic, using the impedance tube, based on the standard ISO10534-1 (1996). The results of the sound absorption coefficient of the analysis showed that the composite fiber rod can be used as an acoustic absorption material, depending on the composition of the composite, it was equivalent to some of the noise absorbing materials market